Repetitive peripheral magnetic stimulation combined with transcranial magnetic stimulation in rehabilitation of upper extremity hemiparesis following stroke: a pilot study - Sijie Liang; Weining Wang; Fengyun Yu; Li Pan; Dongyan Xu; Ruiping Hu; Shan Tian; Jie Xiang; Yulian Zhu (Medical Journals Sweden, 2024)
Objective: To investigate the effect of combined repetitive peripheral magnetic stimulation and transcranial magnetic stimulation on upper extremity function in subacute stroke patients. Design: Pilot study. Subjects: Subacute stroke patients. Methods: Included patients were randomized into 3 groups: a central-associated peripheral stimulation (CPS) group, a central-stimulation-only (CS) group, and a control (C) group. The CPS group underwent a new paired associative stimulation (combined repetitive peripheral magnetic stimulation and transcranial magnetic stimulation), the CS group underwent repetitive transcranial magnetic stimulation, and the C group underwent sham stimulation. All 3 groups received physiotherapy after the stimulation or sham stimulation. The treatment comprised 20 once-daily sessions. Primary outcome was the Fugl-Meyer Assessment Upper Extremity (FMA-UE) score, and secondary outcomes were the Barthel Index and Comprehensive Functional Assessment scores, and neurophysiological assessments were mainly short-interval intracortical inhibition. A 3-group (CPS, CS, C) × 2-time (before, after intervention) repeated measures analysis of variance was conducted to determine whether changes in scores were significantly different between the 3 groups. Results: A total of 45 patients were included in the analysis. Between-group comparisons on the FMA-UE demonstrated a significant improvement (group × time interaction, F2,42 = 4.86; p = 0.013; C vs CS, p = 0.020; C vs CPS, p = 0.016; CS vs CPS, p = 0.955). Correlation analysis did not find any substantial positive correlation between changes in FMA-UE and short-interval intracortical inhibition variables (C, r = -0.196, p = 0.483; CS, r = -0.169, p = 0.546; CPS, r = -0.424, p = 0.115). Conclusion: This study suggests that the real-stimulus (CS and CPS) groups had better outcomes than the control (C) group. In addition, the CPS group showed a better trend in clinical and neurophysiological assessments compared with the CS group.